URGENCY PROVISION OF SEA WATER TREATMENT INVESTMENT LEVY WITH SWRO TECHNOLOGY - Wulandari, Ratih; Hirsanuddin, Hirsanuddin; Asikin, Zainal (Tadulako University, 2019)
Indonesia is a country with a million potential of profitable natural resources. This archipelago country is also a country with abundant water richness but still often occurs scarcity of clean water one of which happened in Gili Trawangan, North Lombok regency of West Nusa Tenggara province. To overcome the lack of access to clean water, PT. Berkat Air Laut conducting investment activities of seawater into freshwater/clean water with desalination technique through the technology of Sea Water Reverse Osmosis (SWRO). Unfortunately, the investment process is always experiencing obstacles in the licensing process due to the absence of provisions regarding the redistribution of such activities. The purpose of this research is to analyse sea water treatment investments with SWRO technology related to the legal void of regional retribution. The methods used are approach to statutory regulations, approach to concepts and approach of the case. These approaches are used to analysts form legal certainty regarding the imposition of seawater retribution.Â The results of the research obtained is that the Law No. 7 of 2004 on water resources has been cancelled by the Constitutional Court of Indonesia as well as stating the re-enactment of Law No. 11 year 1974 of Irrigation but these laws are not comprehensive to accommodate any water resources related activities. Then, other related rules such as Law No. 28 of 2009 on Regional Taxes and Retribution, Regulation of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia No. 47/PERMEN-KP/2016 on the Utilization of Water Conservation Area, West Nusa Tenggara Provincial Regulation No. 12 year 2017 about the Plan Zoning of Coastal Regions and Small Islands of West Nusa Tenggara in 2007-2037 and other special rules do not explain the provisions regarding the levy on sea water treatment so that the void of law needs to be new legislation related to water resources.